Comparison of Visual Functions of Two Amazonian Populations: Possible Consequences of Different Mercury Exposure - Lacerda, Eliza Maria da Costa Brito; Souza, Givago da Silva; Cortes, Maria Izabel Tentes; Rodrigues, Anderson Raiol; Pinheiro, Maria Conceição Nascimento; Silveira, Luiz Carlos de Lima; Ventura, Dora Fix (Frontiers in Neuroscience, 2020)
The present study investigated the visual perimetry and color vision of two Amazonian populations differently exposed to mercury. Ten riverines environmentally exposed to mercury by fish eating and 34 gold-miners occupationally exposed to mercury vapor. The visual perimetry was estimated using the Förster perimeter and the color vision was evaluated using a computerized version of Farnsworth–Munsell test. Riverine and gold-miners’ hair mercury concentrations were quantified. Mercury hair concentration of the riverines was significantly higher than that from gold-miners. Riverines had lower perimetric area than the gold-miners. The errors in the hue ordering test of both Amazonian populations were larger than the controls (non-exposed subjects), but there was no difference between themselves. Riverines had significant multiple association between the visual function and hair mercury concentration, while the gold-miners has no significant association with the exposure. We concluded that the different ways of mercury exposure led to similar visual outcomes, with greater impairment in riverines (organic mercury exposed subjects).